The Assessment of Background Parenchymal Enhancement (BPE) in a High-Risk Population: What Causes BPE? - Chao You; Anna K. Kaiser; Pascal Baltzer; Julia Krammer; Yajia Gu; Weijun Peng; Stefan O. Schönberg; Clemens G. Kaiser (Translational Oncology, 2018)
OBJECTIVE: To investigate promoting factors for background parenchymal enhancement (BPE) in MR mammography (MRM). METHODS: 146 patients were retrospectively evaluated, including 91 high-risk patients (50 BRCA patients, 41 patients with elevated lifetime risk). 56 screening patients were matched to the high-risk cases on the basis of age. The correlation of BPE with factors such as fibroglandular tissue (FGT), age, menopausal status, breast cancer, high-risk precondition as well as motion were investigated using linear regression. RESULTS: BPE positively correlated with FGT (P < .001) and negatively correlated with menopausal status (P < .001). Cancer did not show an effect on BPE (P > .05). A high-risk precondition showed a significant impact on the formation of BPE (P < .05). However, when corrected for motion, the correlation between BPE and a high-risk precondition became weak and insignificant, and a highly significant association between BPE and motion was revealed (P < .01). CONCLUSION: BPE positively correlated with FGT and negatively correlated with age. Cancer did not have an effect on BPE. A high-risk precondition appears to have a negative effect on BPE. However, when corrected for motion, high-risk preconditions became insignificant. Technical as well as physiological influences seem to play an important role in the formation of BPE.